2019
DOI: 10.1002/bit.27202
|View full text |Cite
|
Sign up to set email alerts
|

Xylose assimilation enhances the production of isobutanol in engineered Saccharomyces cerevisiae

Abstract: Bioconversion of xylose—the second most abundant sugar in nature—into high‐value fuels and chemicals by engineered Saccharomyces cerevisiae has been a long‐term goal of the metabolic engineering community. Although most efforts have heavily focused on the production of ethanol by engineered S. cerevisiae, yields and productivities of ethanol produced from xylose have remained inferior as compared with ethanol produced from glucose. However, this entrenched focus on ethanol has concealed the fact that many aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…Meanwhile, we found that SC105 produced much lower carotenoid (20.2 mg L −1 ) when xylose was used as the sole carbon source than using mixed sugars (Figure 4). This result was different from that obtained in a previous work where the production yield from xylose shown remarkable improvement than that from glucose Lane et al, 2020). We also found that strains almost could not grow on YP medium without sugars (Figure 5A).…”
Section: Engineering Hexose Transporter Gal2 For Improving Xylose Asscontrasting
confidence: 99%
“…Meanwhile, we found that SC105 produced much lower carotenoid (20.2 mg L −1 ) when xylose was used as the sole carbon source than using mixed sugars (Figure 4). This result was different from that obtained in a previous work where the production yield from xylose shown remarkable improvement than that from glucose Lane et al, 2020). We also found that strains almost could not grow on YP medium without sugars (Figure 5A).…”
Section: Engineering Hexose Transporter Gal2 For Improving Xylose Asscontrasting
confidence: 99%
“…Greater yields may also be possible when the yeast is engineered to effectively assimilate pentose sugars, which make up 1-2% of the sugars in the present in the mash. Some progress has been made on improving the conversion of xylose to isobutanol in S. cerevisiae but to date yields remain low and there has been no effective demonstration of the conversion of pentose sugars from a mixed carbon feedstock [9,42,43]. This may also open the possibility of using cellulosic and hemicellulosic materials as feedstock.…”
Section: Discussionmentioning
confidence: 99%
“…Most butanol and isobutanol are currently synthesized from petrochemicals, however, Clostridium acetobutylicum will naturally produce 1-butanol and Saccharomyces cerevisiae, bacteria and cyanobacteria have been engineered to produce these alcohols [4][5][6][7][8]. Isobutanol production by E. coli and S. cerevisiae has used glucose as feedstock but microbial strains have been engineered to achieve isobutanol synthesis from xylose, cellulose, methanol, cheese whey and acetate [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lane et al coupled the mitochondrial isobutanol biosynthetic pathway with xylose consumption via the XR-XDH pathway, leading to increased isobutanol yields and titers. [70] The resulting strain produced 2.6 g L −1 isobutanol using xylose as a carbon source in batch flask and bioreactor fermentations. Apart from the slow rates of sugar consumption, the enhanced levels of isobutanol or 2-methyl-1-butanol production in both studies were also attributed to the alleviation of glucose repression on mitochondrial biogenesis and function by xylose utilization.…”
Section: Pyruvate-derived Productsmentioning
confidence: 99%
“…[68] Apart from the diminished overflow metabolism, recent studies producing isobutanol in mitochondrion also attributed the improved production from xylose to the activation of mitochondrial biogenesis and activity, which was repressed by glucose. [69,70] Thus, more mitochondrion-targeted biosynthesis may benefit from xylose utilization.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%